2019
DOI: 10.1111/efp.12515
|View full text |Cite
|
Sign up to set email alerts
|

Culture‐based methods using low‐temperature incubation revealed cold‐adapted fungal endophytes from semiarid forests

Abstract: Fungal endophytes are an important part of the plant microbiome and participate in maintaining the stability of ecosystems. Culture‐based methods are frequently considered in studying fungal communities because of their advantages in providing cultures for further experiments and their low cost. In comparison with next‐generation sequencing methods, their ability to assess fungal diversity is questionable. Here, we show how using two different incubation temperatures can improve the yield of fungal endophytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Endophytes in several unexplored environments around the globe have been intensively studied (Chauhan et al 2019;Fouda et al 2021;Hagh Doust et al 2019;Kamat et al 2020;Singh and Dubey 2018). A little work has been done in this area from Jammu & Kashmir region to exploit the potential of the hidden treasure of indigenous plant endophytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endophytes in several unexplored environments around the globe have been intensively studied (Chauhan et al 2019;Fouda et al 2021;Hagh Doust et al 2019;Kamat et al 2020;Singh and Dubey 2018). A little work has been done in this area from Jammu & Kashmir region to exploit the potential of the hidden treasure of indigenous plant endophytes.…”
Section: Discussionmentioning
confidence: 99%
“…Lipases have emerged as one of the leading biocatalysts in recent years, accounting for almost 10% of the enzyme market, and have shown the ability to add to the multibillion-dollar market share of the bioindustry. These are used as avor-modifying enzymes in food additives, cleaning agents in detergents, pitch control in the paper, digestive enzymes in pharmaceutical products, etc (Carvalho et al 2015;Guerrand 2017;Kumari et al 2019;Raveendran et al 2018;Salihu et al 2016;Singh et al 2016). Among the microbial sources of unique enzymes, the intent for screening bacterial endophytes as a prospective source of such enzymes refers to the hypothesized mutualistic connection between the endophyte and its host plant.…”
Section: Introductionmentioning
confidence: 99%
“…Lower temperatures and longer incubation periods may facilitate species recovery by reducing the growth of fast-growing mesophilic fungi as well as reducing the drying out of culture media. Hagh Doust et al [88] isolated endophytes using two incubation temperatures (4 • C and 25 • C) and they found that using low temperature (4 • C) can increase the numbers of fungal endophytes isolated. This allowed psychrophilic and psychrotolerant fungi to be discovered.…”
Section: Period Of Incubationmentioning
confidence: 99%